MSME Assistance through the Utilization of Digital Marketing on the E-Commerce Platform in Indramayu Regency - Wawan Supriyanto; Tarjono Tarjono; Gilang Bhirawa Noraga (Jurnal Pengabdian Pancasila (JPP), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving Indonesia’s economic growth. However, many MSMEs still face challenges in adapting to digital technology, particularly in marketing. This community service project aimed to assist MSME actors in Indramayu Regency through training and the implementation of digital marketing strategies on e-commerce platforms such as Google My Business, Shopee, and Tokopedia. The approach used was Participatory Action Research (PAR), involving training sessions, discussions, and hands-on practice. The results showed improved understanding among MSMEs regarding the use of digital marketing, optimization of e-commerce platform features, and increased visibility and potential sales of their products. With proper guidance, MSMEs can expand their market reach, enhance competitiveness, and strengthen their role in the digital economy. This program is recommended for replication in other regions to accelerate the digital transformation of MSMEs.